Intralymphatic CD30+ T‐cell proliferation during DRESS: a mimic of intravascular lymphoma. (22nd August 2016) - Weingertner, Noëlle; Mitcov, Mona; Chenard, Marie‐Pierre; Cribier, Bernard
Abstract : Introduction: We describe the case of a patient presenting with drug rash with eosinophilia and systemic symptoms (DRESS), where cutaneous biopsy revealed intravascular atypical lymphocytes suggestive of lymphoma. Case report: A 77‐year‐old man was treated with antibiotics for a hip prosthesis infection. Eight weeks later, he developed a maculo‐papulous eruption, edema of the extremities, fever and blood eosinophilia. Cutaneous biopsy revealed an atypical T‐cell proliferation into the dermal lymphatic vessels. The lymphocytes were mid‐sized, with mitoses and apoptotic figures. They were CD3+, CD4+, CD5+ and some were CD30+. There was no T‐cell receptor (TcR) clonal rearrangement. Complete regression of cutaneous eruption and eosinophilia was observed after ceasing treatment with antibiotics. The diagnosis was that of a benign atypical intralymphatic T‐cell proliferation associated with DRESS. Discussion: The occurrence of atypical dermal CD30+ T‐cells in cutaneous biopsy during benign reactive conditions such as arthropod bites or scabies is well‐known. The intralymphatic localization of such atypical reactive lymphocytes is much less common and represents a diagnostic pitfall because it can suggest aggressive intravascular lymphoma. Conclusion: We report the first case of benign atypical intralymphatic CD30+ T‐cell proliferation associated with DRESS. Diagnostic clues include immunohistochemistry, absence of TcR clonal rearrangement, and anatomo‐clinical correlation.